Kepuasan Konsumen pada Rumah Makan Modern Muara Kapuas dan Rumah Makan Tradisional Yu Sri di Kabupaten Sleman - Sri Larasati (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2012)
The restaurant is one of the businesses that is considered as an endless business. It is because a restaurant fulfils human’s need for food every day. Consequently. the more population live in the area, the higher demand for food. It causes the development of the restaurant industry in Yogyakarta to be more rapid. The study is conducted with the purpose to know the consumer satisfaction level of Muara Kapuas restaurant and Yu Sri restaurant and to test the satisfaction differences perceived by the consumers between Muara Kapuas restaurant and YU Sri restaurant. The result of the study shows that consumers are satisfied with the services provided by Muara Kapuas. The customer's Satisfaction in sequence starting from the biggest the service quality, amenity quality, accessibility quality and product quality. The consumers are satisfied with the YU Sri restaurant service. The customer satisfaction of Yu Sri restaurant in sequence starting from the biggest is product quality, service quality, amenity quality and accessibility quality. The analysis result of the customer's satisfaction differences is found between Muara Kapuas is a restaurant and YU Sri restaurant. In the services quality aspect, amenity quality and accessibility quality, the satisfaction level of that of the Muara Kapuas restaurant is higher than the customers of YU Sri restaurant. While in the product quality aspect, The Yu Sri restaurant consumers have satisfaction level than that of the Muara Kapuas Restaurant consumers.